(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents a brief analysis of the geoecological approach and methods for assessing the representativeness of a network of protected natural areas (PAs), as well as the results of studies conducted in the administrative regions of the Fergana Valley of the Republic of Uzbekistan. Therefore, the existing network of protected areas was analyzed by administrative districts based on the following indicators: level of coverage, preservation of natural geosystems and provision of the territory with environmental objects.